Small business tax secrets : - Carter, Gary W. (J. Wiley, 2003)
TAKE CARE OF YOUR TAXES, BEFORE THEY TAKE CARE OF YOU In a direct and easy-to-use style, the Savvy Savings Guide series offers great financial advice for both your personal and professional life. With each new book, you'll learn how to earn more, spend less, and save for important events such as retirement and your child's college education. From paying less on your taxes to starting a small business the Savvy Savings Guide series will help you save money and succeed! Small Business Tax Secrets addresses a variety of tax issues that every small business must face. Here's how to: Avoid costly tax mistakes and missed opportunites Navigate the details of the new tax laws and IRS rules Increase your knowledge of deductible expenses Keep your records up to IRS standards Organize and run a small business for maximum tax benefits Make filing easy by utilizing sample tax forms The J.K. Lasser Institute is the leading publisher of money and business advice. Each year, millions of Americans trust the J.K. Lasser Institute to help them make the right financial decisions-from making more money today to saving for tomorrow.